2010
DOI: 10.1007/s10339-010-0377-5
|View full text |Cite
|
Sign up to set email alerts
|

Category learning in the context of co-presented items

Abstract: A series of four studies explore how the presentation of multiple items on each trial of a categorization task affects the course of category learning. In a three-category supervised classification task involving multi-dimensionally varying artificial organism-like stimuli, learners are shown a target plus two context items on every trial, with the context items' category membership explicitly identified. These triads vary in whether one, two, or all three categories are represented. This presentation context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Such a conclusion follows other research on the influence of item juxtapositions on learning (Hammer et al, 2009; Andrews et al, 2011). This would support the idea that there is a tendency for humans and animals to readily group together things that look alike (Urcuioli, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…Such a conclusion follows other research on the influence of item juxtapositions on learning (Hammer et al, 2009; Andrews et al, 2011). This would support the idea that there is a tendency for humans and animals to readily group together things that look alike (Urcuioli, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…In the context of geology instruction, for example, Jee, Uttal, and Gentner (2008) demonstrated that studying two highly similar examples that differ only in terms of the presence of a Bfault^improves learning of that concept. In a triad-presentation method, Andrews, Livingston, and Kurtz (2011) found that presenting members of three separate categories simultaneously on each trial led to better learning than presenting three members of the same category.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In one line of work (Andrews, Livingston, & Kurtz, 2011), learners were given the opportunity to compare a target item to two co-presented context items during each trial of a classification learning task based on three categories and continuous valued dimensions. It is a natural prediction that comparison of same-category items ought to promote a generative learning style in the sense of using the comparison opportunity to help discover the commonalities shared by members of each category.…”
Section: Alternatives To Learning Categories One Example At a Timementioning
confidence: 99%